2020
DOI: 10.26905/jkdp.v24i2.4061
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomics fluctuations and its impact on musharaka financing

Abstract: This study aims to analyze the effect of the movement of macroeconomic variables on financing using the musharaka contract on Islamic banks. This study consists of sharia commercial banks and sharia business units using monthly data from January 2004 to December 2019. This study uses Vector Error Correction Model (VECM) to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Inflation is one of the government's indicators in making monetary policy. The increase in inflation will be responded to by an increase in interest rates, which means increasing the price of financing in the banking sector (including Islamic banks) (Mubarok et al, 2020). The high inflation will eventually cause a decline in the distribution of financing, including profit-sharing financing.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflation is one of the government's indicators in making monetary policy. The increase in inflation will be responded to by an increase in interest rates, which means increasing the price of financing in the banking sector (including Islamic banks) (Mubarok et al, 2020). The high inflation will eventually cause a decline in the distribution of financing, including profit-sharing financing.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Many factors can influence banks in channeling their financing, both internal and external factors. There are several ways to identify factors that can affect profit-sharing financing as has been done by previous researchers, including the influence of mudharabah deposits (Kiswanto, 2013;Pramono, 2013;Riyanto, 2016), the influence of non-performing financing (Arnan & Kurniawasih, 2014;Kurniawanti & Zulfikar, 2014;Annisa & Yaya, 2015;Destiana, 2016;Jamilah, 2016;Kalkarina et al, 2016;Riyanto, 2016;Murni et al, 2018;Ispad, 2019;Nastiti & Kasri, 2019), equivalent rate (Kiswanto, 2013;Pramono, 2013;Kurniawanti & Zulfikar, 2014;Riyanto, 2016), efficiency (Jamilah, 2016;Nastiti & Kasri, 2019), economic growth (Ayyubi et al, 2017;Anwar et al, 2020;Hafizh et al, 2020) and inflation (Priyanto et al, 2016;Nastiti & Kasri, 2019;Mubarok et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The level of profit sharing has a substantial relationship to the public interest in placing their savings in Islamic banks (Ab Rahman et al, 2021). In addition, profit sharing has been shown to have a positive and significant influence on customers' decisions in choosing to save in Islamic banks (Mubarok, Hamid, & Arif, 2020).…”
Section: Profit-sharing Ratementioning
confidence: 99%
“…According to the authors, low income forces people to access financing. A study by Mubarok et al (2020) showed that an increase in income or purchasing power reduces the Musharaka financing utilization for the case of Islamic banks of Malaysia. Similar results were concluded by Rahayu et al (2016) after interviewing 30 clients of Islamic financial institutions in Indonesia.…”
Section: Demand For Musharakamentioning
confidence: 99%
“…First, studies are silent on the link of their independent variable (whether it increases the demand for or supply of Musharaka). Second, few studies made a correct connection with supply or demand for Musharaka (like Mubarok et al (2020) or Alkhan (2020)). However, they still missed confirmation regarding the convergence of equilibrium.…”
Section: Demand For Musharakamentioning
confidence: 99%